2000
DOI: 10.1002/1097-4628(20001107)78:6<1250::aid-app110>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and elongation on the liquid diffusion and permeation characteristics of natural rubber, nitrile rubber, and bromobutyl rubber

Abstract: The diffusive properties of acetone, dichloromethane, and toluene in natural, nitrile, and bromobutyl rubber membranes at temperatures between 273 and 313 K and uniaxial elongations between 0 and 40% were investigated. As the temperature and elongation increase, the steady state flux increases, and the breakthrough time decreases. An increase in temperature leads to an increase in permeability, and small extensions do not cause significant changes in the diffusive properties. © 2000 John Wiley & Sons, Inc. J A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The increase in flux is in agreement with experimental data, as a larger γ 2 implies a larger effect of E , the elastic diffusion coefficient, on the transport of chemicals through polymeric membranes. This prediction may be useful in explaining previously reported cases of stress‐enhanced transport 10, 11, 14. An increase in γ 2 also increases the time to reach a maximum flux.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The increase in flux is in agreement with experimental data, as a larger γ 2 implies a larger effect of E , the elastic diffusion coefficient, on the transport of chemicals through polymeric membranes. This prediction may be useful in explaining previously reported cases of stress‐enhanced transport 10, 11, 14. An increase in γ 2 also increases the time to reach a maximum flux.…”
Section: Discussionsupporting
confidence: 59%
“…These figures show a profile where the flux has a maximum and will reach steady state at a later time. Experimental work for the permeation of acetone though elongated nitrile rubber and the permeation of dichloromethane through PVC exhibited similar behavior even though the boundary conditions of the experimental data differ from the mathematical model presented in this article 1, 9–11. While the experimental data are associated with a negligible concentration of the permeant on the downstream side of the membrane, this mathematical model considers a constant flux.…”
Section: Discussionmentioning
confidence: 75%
“…Previously, much attention has been paid to the effects of swelling stress on transport of small molecules in crosslinked polymers [33][34][35][36] while only a few studies have been done on external mechanical stress. [37][38][39][40][41][42][43][44] Several factors that affect diffusion of small molecules when the matrix is elongated, including strain levels, change of free volume, molecular orientation and strain-induced crystallization have been studied. Treloar pioneered experimental investigations on the swelling of vulcanized natural rubber by benzene and heptane under mechanical strain and successfully correlated the results with an extension of Flory-Rebner's statistical theory.…”
Section: Introductionmentioning
confidence: 99%
“…Humidity ageing is widely recognized as one of the main cause of long‐term failure of organic composites exposed to the atmosphere or in contact with aqueous media. The humid ageing of the composite materials is ascribed to the moisture absorption, and it has been investigated by assuming that the moisture absorption process follows Fick's law 1–3…”
Section: Introductionmentioning
confidence: 99%
“…Kee et al presented the results of permeation experiments with different solvents into natural, nitrile, and bromobutyl rubber membranes at different temperatures and elongations. Test results showed that an increase in temperature lead to an increase in permeability, and a small extension does not cause a significant change in the diffusive properties 3. Hwang et al have studied the diffusion and absorption behavior of glycidyl metacrylate in styrene butadiene rubber (SBR), using the gravimetric absorption method.…”
Section: Introductionmentioning
confidence: 99%